Effect of long-term remote ischaemic conditioning on platelet function and fibrinolysis in patients with chronic ischaemic heart failure. Issue 153 (May 2017) - Pryds, Kasper; Kristiansen, Jacobina; Neergaard-Petersen, Søs; Nielsen, Roni R.; Schmidt, Michael R.; Refsgaard, Jens; Kristensen, Steen D.; Bøtker, Hans Erik; Hvas, Anne-Mette; Grove, Erik L.
Abstract: Introduction: Remote ischaemic conditioning (RIC) protects against ischaemia-reperfusion injury through cellular protective pathways, but may also modulate haemostasis. We aimed to investigate the effect of long-term RIC on platelet function and fibrinolysis in patients with chronic ischaemic heart failure (CIHF). Material and methods: In a prospective, outcome-assessor blinded, paired study, 16 patients with CIHF and 21 age- and gender-matched controls without ischaemic heart disease (IHD) were treated with RIC once daily for 28 ± 4 days. RIC was performed as four cycles of 5 min upper arm ischaemia and reperfusion. We evaluated collagen and arachidonic acid induced platelet aggregation (Multiplate® Analyzer), platelet turnover (Sysmex® XE-5000), platelet activation (plasma soluble-platelet-selectin) and fibrinolysis (clot lysis time, tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1)). We compared blood samples assessed at baseline and following long-term RIC. Results: Long-term RIC did not affect platelet aggregation, turnover or activation or PAI-1 in any study groups. Long-term RIC did not affect fibrin clot lysis time in patients with CIHF but reduced fibrin clot lysis time in matched controls without IHD (median: 773 s (interquartile range: 689–936) vs. 658 s (618–823), p = 0.03). t-PA was increased following long-term RIC in CIHF patients (2.5 (1.7–3.4) vs. 2.9 (1.8–4.0), p = 0.03) and in matched controls without IHD (1.5 (1.3–1.9) vs. 1.6 (1.4–2.3), p = 0.03). Conclusions: While long-term RIC did not affect collagen or arachidonic acid induced platelet aggregation, platelet turnover or sP-selectin, fibrinolysis was increased although most consistently in matched controls without IHD. This finding suggests that RIC may stimulate fibrinolysis potentially reducing the risk of thrombosis. Highlights: Chronic ischaemic heart failure is a frequent disease with poor prognosis. Remote ischaemic conditioning (RIC) may affect platelet aggregation and fibrinolysis. We explored long-term RIC in patients with chronic ischaemic heart failure. We evaluated changes in platelet aggregation and fibrinolysis after long-term RIC. Long-term RIC may stimulate fibrinolysis.